Determinants of self-rated health of Francophone seniors in a minority situation in Canada - Alimezelli, Hubert; Leis, Anne; Karunanayake, Chandima; Denis, Wilfrid (Minorités linguistiques et société / Linguistic Minorities and Society, 2013)
Current trends show that governments and health institutions in Canada and other developed nations are responding inadequately to the growing need for health services of the increasingly aging population. The Analysis of Statistics Canada’s 2006 post-census Survey on the Vitality of Official Language Minorities show that in addition to age and other socio-demographic determinants, linguistic barriers affect the self-rated health of seniors of official languages living in a minority situation. This study suggests among other things a greater understanding of Official language minorities’ contextual realities, the improvement of both the linguistic environment and services in the minority language.